Assessment of Socio-Economic Well-Being in European Countries: A Multidimensional Comparative Analysis - Justyna KUJAWSKA (Communications of International Proceedings, 2025)
The aim of this study is to assess the level and differentiation of socio-economic well-being across European countries belonging to the European Union and the European Free Trade Association (EFTA). The analysis covered nine diagnostic variables representing multiple dimensions of well-being, including social, economic, educational, health, and environmental factors. Statistical data were obtained from Eurostat databases and refer to the year 2022. Synthetic composite indicators were constructed using the Hellwig and TOPSIS methods to enable a comparative evaluation of countries in terms of their overall well-being. The results revealed that Northern and Western European countries (including Norway, Sweden, the Netherlands, and Finland) form a cluster characterized by the highest level of well-being and social equilibrium, while South-Eastern European countries (such as Greece and Latvia) exhibit lower levels of development and a higher housing cost burden. The correlation between the two methods (Pearson’s r = 0.72) indicates a moderate but consistent relationship, confirming the robustness of the obtained rankings. Furthermore, the Ward’s hierarchical clustering method distinguished four groups of countries with similar development profiles, highlighting the persistent regional disparities within Europe.
Keywords: quality of life; well-being; composite indicators; multivariate analysis; European countries.